Psychological capital: A positive resource for combating employee stress and turnover - Avey, James B.; Luthans, Fred; Jensen, Susan M. (Human Resource Management, 2009)
AbstractWorkplace stress is a growing concern for human resource managers. Although considerable scholarly and practical attention has been devoted to stress management over the years, the time has come for new perspectives and research. Drawing from the emerging field of positive organizational behavior, this study offers research findings with implications for combating occupational stress. Specifically, data from a large sample of working adults across a variety of industries suggest that psychological capital (the positive resources of efficacy, hope, optimism, and resilience) may be key to better understanding the variation in perceived symptoms of stress, as well as intentions to quit and job search behaviors. The article concludes with practical strategies aimed at leveraging and developing employees' psychological capital to help them better cope with workplace stress. © 2009 Wiley Periodicals, Inc.